A PdII Carbene Complex with Anthracene Side‐Arms for π‐Stacking on Reduced Graphene Oxide (rGO): Activity towards Undirected C–H Oxygenation of Arenes. Issue 43 (21st November 2018) - Majeed, Maitham H.; Shayesteh, Payam; Persson, Axel R.; Wallenberg, L. Reine; Schnadt, Joachim; Wendt, Ola F.
Abstract : An N‐heterocyclic carbene palladium(II) complex containing two anthracene side arms was immobilized on the surface of reduced graphene oxide (rGO) by π‐stacking. The activity of the homogeneous analogue and the supported complex in undirected C–H acetoxylation reaction of arenes was studied. The results show that the catalytic efficiency in acetoxylation of benzene is improved in the immobilized materials compared to the homogeneous analogue. According to XPS analysis, the immobilized catalyst maintains the original oxidation state of Pd II after the catalytic reaction. Abstract : π‐Stacking an NHC Pd system with anthracene side arms on a reduced graphene oxide surface is a simple procedure and gives a material that is an effective, recyclable catalyst in the acetoxylation of benzene. The complex remains molecular palladium(II) also on the graphene surface and the activity is comparable to other supported NHC–Pd complexes with more elaborate support procedures.